Integrating Javanese in Social Studies at Madrasah Ibtidaiyah Muhammadiyah Bulak - Rochmawan, Alfian Eko; Maemonah, Maemonah; Abbas, Ngatmin (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
The fundamental reason for this research is the need to enhance students’ understanding of the subject matter while preserving and strengthening local cultural identity amidst globalization. This study aims to analyze the implementation and impact of using the Javanese language in Social Studies (IPS) instruction at Madrasah Ibtidaiyah Muhammadiyah Bulak, Gondangrejo District, Karanganyar Regency. The research method used is qualitative, with a case study approach involving classroom observations, in-depth interviews with teachers and the headmaster, and document analysis. The research results show that the use of the Javanese language in social studies instruction varies at each grade level and is adapted to the student’s cognitive levels. This approach has proven effective in enhancing students’ understanding of Social Studies material, especially concepts related to the local socio-cultural context. The use of the Javanese language also plays a crucial role in language preservation and strengthening students’ cultural identity. Despite challenges in its implementation, such as balancing with the Indonesian language, this strategy overall creates holistic learning, improves academic understanding, and strengthens students’ social skills. These findings have significant implications for the development of curricula and learning strategies that are responsive to the local cultural context.